Keterwakilan Perempuan pada Pemilihan Anggota Dewan Perwakilan Rakyat Kabupaten Tulang Bawang Barat pada Pemilihan Umum (Pemilu) 2019 - Hervina, Ari; Hertanto, Hertanto; Warganegara, Arizka (Journal of Research in Social Science and Humanities, 2021)
The breakthrough to achieve justice in the political field is the implementation of an affirmative action system, which is a system used globally to enable women to play their role, especially in the world of politics. The purpose of this research is to find out, analyze and explain what factors influence women's representation in the West Tulang Bawang Regency DPRD election results in 2019 and to find out, analyze and explain strategies for increasing women's representation in PDIP, Nasdem Party and Gerindra Party. As for those who became respondents in this study amounted to 7 people. The results of this research are 1) The factors that influence women's representation in the Legislative Election DPRD Tulang Bawang Barat Regency are 3 (three), namely political education, political communication and political culture and the most dominant factor influencing is "patriarchal culture" with the conclusion explanation as follows: The following: 1) Political education: political education efforts for legislative candidates, especially women, are not effectively implemented, this is due to time constraints and the reluctance of women legislative candidates to access and deepen knowledge about the world of politics, b) Political communication: political communication efforts the majority of legislative candidates only rely on the media mix and are less effective in direct political communication or interpersonal communication such as open campaigns or door to door. c) Political culture: patriarchal culture is still cultured, namely a culture that places women in a position that is always under men, is considered to have duties and responsibilities in domestic management of the household, namely kitchens, wells and mattresses. And 2) The strategy to increase women's representation in PDIP, Nasdem Party and Gerindra Party is carried out in 3 (three) ways, namely a) Increasing political education, b) Increasing political marketing and c) Increasing women's political participation.